The Folklore of "Putri Mandalika" in Implementing Islamic Religious Education Learning - Murdianto Murdianto (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The research objective is to provide knowledge to students in particular, and the wider community in general about folklore or folklore entitled 'Princess Mandalika' originating from the Sasak tribe in learning Islamic religious education based on local wisdom. The research method used in this study is descriptive qualitative, and observation, interviews and documentation are the data collection techniques used. The researcher analyzes the data by collecting data, reducing the data that has been collected by taking important data and discarding unimportant data. Finally, the researcher draws conclusions according to the data in the field. As for the results of this study that local wisdom can be grown in students in teaching and learning activities (KBM) at school starting from 07:15-12:00, in Mulok lessons will be included a lesson about folklore entitled 'putri mandalika', as well as asking students to find moral messages related to learning Islamic religious education in the story. The growth of local wisdom in students is carried out through a learning process.